VD_FINDINFO HC / 2011 / 180 vom 11. April 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, HEURES DE TRAVAIL NON EFFECTUÉES | 324 CO, 337 CO, 444 CPC, 445 CPC, 451 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 466 al. 1 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 405 al. 1 CPC (CH)